Appendicular peritonitis in situs inversus totalis: a case report - Cissé, Mamadou (BioMed Central, 2010)
INTRODUCTION: Situs inversus is a congenital anomaly characterized by the transposition of the abdominal viscera. When associated with dextrocardia, it is known as situs inversus totalis. This condition is rare and can be a diagnostic problem when associated with appendicular peritonitis. CASE PRESENTATION: We report the case of a 20-year-old African man who presented to the emergency department with a 4-day history of diffuse abdominal pain, which began in his left iliac region and hypogastrium. After examination, we initiated a surgical exploration for peritonitis. We discovered a situs inversus at the left side of his liver, and his appendix was perforated in its middle third. A complementary post-operative thoracic and abdominal tomodensitometry revealed a situs inversus totalis. CONCLUSION: Appendicular peritonitis in situs inversus is a rare association that can present a diagnostic problem. Morphologic exploration methods such as ultrasonography, tomodensitometry, magnetic resonance imaging, and laparoscopy may contribute to the early management of the disease and give guidance in choosing the most appropriate treatment for patients.